A relação dinâmica entre receita e despesa governamentais para Região Nordeste - Azevedo, Mauro Jorge Mafra (2010)
The recent increase in the importance of public sector in the economy and the need for greater control over budget deficits in the federal and local government became a discussion on the relationship between government revenue and expenditure of a theme prominent among political scientists and economists. This study evaluates the impact of the Law of Fiscal Responsibility (LRF) in the dynamic relationship between government revenue and expenditure for the northeastern counties. It was found that revenues cause expenditures to Granger, where the past revenue also influence the behavior of the current running costs. It was concluded that before the introduction of the LRF, municipalities directioned its attention on controlling your own revenue for current expenses and, consequently, their public deficits . Therefore addition, it has increased the bargaining power of the counties along the northeastern legislative, which took into account in calculating the amount of lending to municipalities, how they are charged by cost. This fact evidence, a possible improvement in public accounts of these cities, after the LRF.